Characterisation of radiation damage in W and W-based alloys from 2 MeV self-ion near-bulk implantations. (15th June 2015) - Yi, Xiaoou; Jenkins, Michael L.; Hattar, Khalid; Edmondson, Philip D.; Roberts, Steve G.
Abstract: The displacement damage induced in W and W-5 wt.% Re and W-5 wt.% Ta alloys by 2 MeV W + irradiation to doses 3.3 × 10 17 –2.5 × 10 19  W + /m 2 at temperatures ranging from 300 to 750 °C has been characterised by transmission electron microscopy. An automated sizing and counting approach based on Image J (a Java-based image processing programme developed at the National Institutes of Health) [1] has been performed for all near-bulk irradiation data. In all cases the damage comprised dislocation loops, mostly of interstitial type, with Burgers vectorsb  = 1/2〈1 1 1〉 (>60%) andb  = 〈1 0 0〉. The diameters of loops did not exceed 20 nm with most being ⩽6 nm diameter. The loop number density varied between 10 22 and 10 23  loops/m 3 . With increasing irradiation temperature, the loop size distributions shifted towards larger sizes, and there was a substantial decrease in loop number densities. The damage microstructure was less sensitive to dose than to temperature. Under the same irradiation conditions, loop number densities in the W-Re and W-Ta alloys were higher than in pure W but loops were smaller. In grains with normals close toz  = 〈0 0 1〉, loop strings developed in pure W at temperatures ⩾500 °C and doses ⩾1.2 dpa, but such strings were not observed in the W-Re or W-Ta alloys. However, in other grain orientations complex structures appeared in all materials and dense dislocation networks formed at higher doses.